Limited Utility of Circulating Cell-Free DNA Integrity as a Diagnostic Tool for Differentiating Between Malignant and Benign Thyroid Nodules With Indeterminate Cytology (Bethesda Category III) - Thakur, Shilpa; Tobey, Andrew; Daley, Brianna; Auh, Sungyoung; Walter, Mary; Patel, Dhaval; Nilubol, Naris; Kebebew, Electron; Patel, Aneeta; Jensen, Kirk; Vasko, Vasyl; Klubo-Gwiezdzinska, Joanna (Frontiers in Oncology, 2019)
Background: Analysis of plasma circulating cell-free DNA integrity (cfDI) has emerged as a promising tool in the diagnosis of malignant vs. benign tumors. There is limited data on the role of cfDI in thyroid cancer. The goal of this study was to analyze cfDI as a biomarker of malignancy in patients with cytologically indeterminate thyroid nodules. Methods: The cfDI was measured in the plasma of patients with cytologically indeterminate thyroid nodules. All patients underwent plasma collection within 24–72 h before surgical treatment for thyroid nodules. Additionally, samples were collected from seven patients via the vein draining the thyroid and peripheral vein during surgery. Quantitative real-time PCR was performed on the isolated cell-free DNA using two different primer sets (115 and 247 bp) to amplify consensus ALU sequences. The cfDI was calculated as the ratio of ALU247 to ALU115. Results: All data are given as median [25th−75th percentile]. The study group consisted of 67 patients with 100 nodules, 80.6% (54/67) women, aged 43 [33-60] years. There was no difference in cfDI between 29 patients with benign nodules (0.49 [0.41–0.59]) and 38 patients with malignant lesions (0.45 [0.36–0.57], p = 0.19). There was no difference in cfDI in the vein draining the thyroid (0.47 [0.24–1.05]) and peripheral vein (0.48 [0.36–0.56], p = 0.44). In comparison to thyroid cancer patients, patients with benign nodules were characterized by significantly higher concentrations of ALU115 (1,064 [529–2,960] vs. 411 [27–1,049] ng/ml; p = 0.002) and ALU247 (548 [276–1,894] vs. 170 [17-540] ng/ml; p = 0.0005), most likely because benign tumors were larger (3, [1.8–4.1 cm]) than malignant lesions (0.7 [0.23–1.45], p < 0.0001). Women had significantly lower cfDI (0.45 [0.27–0.54]) than men (0.56 [0.44–0.8], p = 0.011). Conclusion: The cfDI measured in the vein draining the thyroid is similar to the cfDI measured in the antecubital vein, validating cfDI measurements by peripheral liquid biopsy. Analysis of cfDI needs to be stratified by patients gender. In contrast to its diagnostic utility in aggressive cancers, cfDI has limited utility as a biomarker of malignancy in cytologically indeterminate thyroid nodules.